DETERMINATION OF FLAVONOID LEVELS OF AlCl3 METHODE IN THE EXTRACT OF METANOL FLOWERS (Clitoria ternatea L.) - Anita Agustina Styawan; Gandis Rohmanti (Universitas Muhammadiyah Magelang, 2020)
Telang flowers is one of the medicinal plants that can grow well in Indonesia, but have not been widely used. Previous research stated that methanol extract of telang flowers had secondary metabolite compounds such as tannin, saponin, flavonoid and alkaloid. Flavonoid are natural compounds that have the potential as antioxidants that can capture free radicals that play a role in the emergence of degenerative diseases throught the mechanisme of damage to the body’s immune system, lipid oxidation and protein.The purpose of this study was to determine whether telang flowers content was determined whether by the AlCl3 method and measured by using UV-Vis Spektrophotometry from the methanol extract of telang flowers.The results of this study indicate that the methanol extract of telang flowers contains flavonoid with red color. The level of flavonoids intended is 4.65%.